8 The Statutes at Large of Pennsylvania from 1682 to 1801, at 492 (1902) - (:unkn) unknown (My University, 1755)
Provided "that it be recommended to all male white persons within this province, between the ages of sixteen and fifty years, who have not already associated, and are not conscientiously scrupulous of bearing arms, to join the said [militia] association immediately."
Keywords: MILITIAS